USE OF SOCIAL MEDIA PLATFORMS AND PURCHASE DECISIONS FOR DIGITAL ACCESSORIES AMONG CUSTOMERS IN SAN JUAN DE LURIGANCHO, LIMA - Vega Garcia, Jhon Andre; Medina Gamero, Aldo (LACCEI, 2025)
This study analyzes the correlation between social platforms and the purchase decision of digital accessories among shoppers in San Juan de Lurigancho. Given the growing impact of social media platforms such as YouTube, Instagram, Facebook, and TikTok, which has grown exponentially in recent years, on consumer behavior, the main objective is to establish whether a significant relationship is evident between the two variables. A quantitative methodological approach was applied, using a non-experimental format, which was studied cross-sectionally, and correlations between variables were analyzed. The sample consisted of 250 people between 18 and 45 years of age, selected through non-probability sampling. The instrument consisted of a questionnaire evaluated through expert judgment using a Likert scale. The data were processed using SPSS. The findings showed a moderate positive correlation between social platforms and purchase decision (r = 0.413; p < 0.001), and low positive relationships between each dimension analyzed. A perfect relationship (r = 1.000) was noted between content connection and purchase choice. It is determined that digital activity influences consumer behavior, with the quality, consistency, and interaction of content on social networks being key to driving purchasing decisions.